Editorial on the Research Topic of the Special Issue “Current Status of Acinetobacter Infections” - Nocera, Francesca Paola; De Martino, Luisa (Pathogens (Basel), 2023)
Emerging bacterial infections will continue to be an important issue for public health, mostly because of the constant changes on our earth [...].Emerging bacterial infections will continue to be an important issue for public health, mostly because of the constant changes on our earth [...].